Chlamydomonas DYX1C1/PF23 is essential for axonemal assembly and proper morphology of inner dynein arms. - Ryosuke Yamamoto; Jagan M Obbineni; Lea M Alford; Takahiro Ide; Mikito Owa; Juyeon Hwang; Takahide Kon; Kazuo Inaba; Noliyanda James; Stephen M King; Takashi Ishikawa; Winfield S Sale; et al. (PLoS Genetics)
Cytoplasmic assembly of ciliary dyneins, a process known as preassembly, requires numerous non-dynein proteins, but the identities and functions of these proteins are not fully elucidated. Here, we show that the classical Chlamydomonas motility mutant pf23 is defective in the Chlamydomonas homolog of DYX1C1. The pf23 mutant has a 494 bp deletion in the DYX1C1 gene and expresses a shorter DYX1C1 protein in the cytoplasm. Structural analyses, using cryo-ET, reveal that pf23 axonemes lack most of the inner dynein arms. Spectral counting confirms that DYX1C1 is essential for the assembly of the majority of ciliary inner dynein arms (IDA) as well as a fraction of the outer dynein arms (ODA). A C-terminal truncation of DYX1C1 shows a reduction in a subset of these ciliary IDAs. Sucrose gradients of cytoplasmic extracts show that preassembled ciliary dyneins are reduced compared to wild-type, which suggests an important role in dynein complex stability. The role of PF23/DYX1C1 remains unknown, but we suggest that DYX1C1 could provide a scaffold for macromolecular assembly.